Evaluation of Culture Methods To Identify Bovine Feces with High Concentrations of Escherichia coli O157 - Fox, J. Trent; Renter, David G.; Sanderson, Michael W.; Thomson, Daniel U.; Lechtenberg, Kelly F.; Nagaraja, T. G. (My University, 2007)
Our objective was to evaluate methods for identifying cattle with high concentrations of Escherichia coli O157 in their feces. In two experiments, feces were collected from cattle orally inoculated with nalidixic acid (Nal)-resistant E. coli O157, and direct plating of diluted feces on sorbitol MacConkey agar with cefixime and potassium tellurite (CT-SMAC) containing Nal was considered the gold standard (GS) method. In experiment 1, methods evaluated were preenrichment direct streak, immunomagnetic separation with most probable number (MPN), and postenrichment direct streak with MPN, all using CT-SMAC. The mean concentration of Nal-resistant E. coli O157 in samples (n = 59) by use of the GS was 3.6 log10 CFU/g. The preenrichment streak detected >3.0 log10 CFU/g samples with a 74.4% sensitivity and 68.8% specificity. Postenrichment direct streak-MPN and immunomagnetic separation-MPN concentrations were correlated significantly with GS concentrations (r = 0.53 and r = 0.39, respectively). In experiment 2 (480 samples), pre- and postenrichment direct streaking performed in triplicate and spiral plating on CT-SMAC were evaluated. For preenrichment streaks, sensitivity was 79.7% and specificity was 96.7% for detecting >3.0 log10 CFU/g when the criterion was positive cultures on at least two plates. For spiral plating at that concentration, sensitivity and specificity were 83.9% and 56.3%, respectively. Postenrichment streaking performed relatively poorly. Triplicate preenrichment streaks of 1:10-diluted feces on CT-SMAC may be useful for identifying cattle shedding high concentrations of E. coli O157. Estimates of sensitivity and specificity enable appropriate application of methods and interpretation of results and may enhance applied research, surveillance, and risk assessments.